Presenting Inclusive Islamic Education: Shaping a Generation that Values Diversity Amidst Globalization - Surawan Surawan; Sarimah Awang (CV. Intake Pustaka, 2026)
Inclusive Islamic education has become a strategic necessity in the era of globalization characterized by cross-cultural, religious, and value interactions. This paper aims to analyze the concept, implementation, and implications of inclusive Islamic education in shaping a generation that values diversity. The research method employs a systematic literature review of reputable international journals and relevant books published since 2015. The study results show that inclusive Islamic education can strengthen the values of tolerance, equality, and respect for cultural and religious differences. An inclusive curriculum and a pedagogical approach that is responsive to diversity are key elements in the implementation. The main challenges include teacher readiness, resources, and resistance to changes in the traditional education paradigm. The implications of this research emphasize the need for curriculum reform, educator training, and educational policies that support the implementation of inclusivity to produce a generation of Muslims capable of playing a role in a plural and dynamic global society.